Cell-free synthesis of functional antibodies using a coupled in vitro transcription-translation system based on CHO cell lysates - Stech, M. (Sci Rep, 2017)
Antibodies are indispensable tools for basic research as well as diagnostic and therapeutic applications. Consequently, the development of alternative manufacturing strategies which circumvent the hurdles connected to conventional antibody production technologies is of enormous interest. To address this issue, we demonstrate the synthesis of complex antibody formats, in particular immunoglobulin G (IgG) and single-chain variable fragment Fc fusion (scFv-Fc), in a microsome-containing cell-free system based on translationally active chinese hamster ovary (CHO) cell lysates. To mimic the environment for antibody folding and assembly present in living cells, antibody genes were fused to an endoplasmic reticulum (ER)-specific signal sequence. Signal-peptide induced translocation of antibody polypeptide chains into the lumen of ER microsomes was found to be the prerequisite for antibody chain assembly and functionality. In this context, we show the rapid synthesis of antibody molecules in different reaction formats, including batch and continuous-exchange cell-free (CECF) reactions, depending on the amount of protein needed for further analysis. In addition, we demonstrate site-specific and residue-specific labeling of antibodies with fluorescent non-canonical amino acids. In summary, our study describes a novel antibody production platform which combines the highly efficient mammalian protein folding machinery of CHO cells with the benefits of cell-free protein synthesis.